Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy